Impact of mentoring on socio‐emotional and mental health outcomes of youth with learning disabilities and attention‐deficit hyperactivity disorder. Issue 4 (21st April 2019) - Haft, Stephanie L.; Chen, Tiffany; LeBlanc, Chloe; Tencza, Francesca; Hoeft, Fumiko
Abstract : Background: Learning disabilities (LD) and attention‐deficit hyperactivity disorder (ADHD) are often accompanied by significant socio‐emotional impairments and mental health challenges. However, there is a lack of controlled, quantitative research on potential interventions to address this issue. The current study evaluated the impact of a near‐peer mentoring program for youth with LD/ADHD designed to promote socio‐emotional well‐being. Methods: Youth with LD/ADHD who participated in the mentoring program (Mentored; n  =   99) were compared to both nonmentored youth with LD/ADHD (Control‐NM; n  =   51) and typically developing youth without LD/ADHD (Control‐TD; n  =   81) prementoring in the fall and postmentoring in the spring. Participants were assessed using self‐report measures of anxiety, depression, interpersonal relations, and self‐esteem. Results: Youth with LD/ADHD showed significantly higher scores of depression and significantly lower scores of interpersonal relations compared to the Control‐TD group at fall baseline. The depression and self‐esteem scores of the Mentored group significantly decreased and increased, respectively, after mentoring. These changes were associated with mentee‐perceived mentorship quality. The Control‐NM group showed significant decreases in both self‐esteem and interpersonal relations, as well as increases in depression over time, while the Control‐TD group remained stable across all measures. Conclusions: Results suggest that mentoring shows promise as a potential intervention for youth with LD/ADHD who experience co‐occurring socio‐emotional and mental health difficulties. The study is the first, to our knowledge, to quantify the effect of a near‐peer mentoring program on youth with LD/ADHD in a design with two control groups. Implications for research and practice involving LD, ADHD, and mental health disorders are discussed. Key Practitioner Message LD and ADHD are associated with increased anxiety, depression, and impaired self‐esteem and interpersonal relationships. There is a lack of research on interventions that could address the mental health problems and socio‐emotional difficulties that co‐occur with learning disabilities and ADHD. Near‐peer mentoring is a promising intervention that can improve socio‐emotional well‐being and mental health in youth with learning disabilities and ADHD, and highlights the importance of strong interpersonal relationships as a protective factor.